Sosialisasi Akuntansi Keuangan Desa di Desa-Desa Kecamatan Bancak Kabupaten Semarang - Sudarman Sudarman; Endang Dwi Wahyuningsih; Mudjiyono Mudjiyono; Hani Krisnawati; Aniqotunnafiah Aniqotunnafiah (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2020)
Accounting information has an important role in achieving business success, including for small businesses. Accounting is one way to produce financial information that can be used by management as a basis for making strategic decisions. Reports produced include balance sheets, profit/loss reports, changes reports and cash flow reports. All of these reports can be used by information users. For small business actors in villages, it is minimal to have accounting records, most of them make business decisions based on experience alone. Small business development is needed to make it strong, both related to development both external to the company and in managing the company's internal. If from an internal perspective, the management of small businesses still considers that the accounting process is still not very important to implement. Empowerment of business management management is very necessary. Good financial reports can provide useful financial information for making strategic business decisions. This community service is expected to increase the ability of business actors in the villages of Bancak District, Semarang Regency so that they can provide information on the financial condition of businesses that are being run for each reporting period. The community service team of ITB Semarang Accounting Study Program lecturers conducted community outreach activities in the form of simple lectures and training. The results of this community service were well received by participants in the Financial Accounting socialization and training for business actors in Bancak District, Semarang Regency.